Oscillatory activity in the pedunculopontine area of patients with Parkinson's disease. - Androulidakis, A; Mazzone, P; Litvak, V; Penny, W; Dileone, M; Gaynor, L; Tisch, S; Di Lazzaro, V; Brown, P (2008)
The pedunculopontine nucleus (PPN) has recently been introduced as a new therapeutic target for deep brain stimulation (DBS) in patients suffering from Parkinson's disease (PD). In a recent case report it was demonstrated that alpha frequency oscillations appear in PPN after the administration of levodopa in PD, indicating a possible physiological role of these oscillations. Here we confirm this result and investigate the functional connectivity and reactivity of subcortical alpha activity by recording LFP activity from the PPN area and EEG in six patients with PD while at rest and in four of them while they performed ipsi- and contralateral self-paced joystick movements. Levodopa strongly promoted 7-11 Hz oscillatory synchronization in the region of PPN and coupling of this activity with similar activity in the cortical EEG. Such coupling was bidirectional. Moreover, the 7-11 Hz oscillatory synchronization in the PPN area increased about 3 s prior to self-paced movements, but only following levodopa treatment. These findings suggest that alpha oscillations in the PPN area may represent a physiological pattern of activity. The subcortical oscillations are coupled to cortical alpha activity and possibly allied to motor related attentional processes.